A study on management of corporate cash in consumer durable sector - Somnath Das (Management Science Letters)
Cash plays essential role in modern business and economy and it is the life blood of all businesses. Therefore, cash management is the art of managing a company’s short-term resources for its ongoing activities, mobilizing funds and optimizing liquidity. Inefficient cash management may lead the company to bankruptcy. In this paper, we highlight different perspectives in which we can control the corporate cash including Cash Conversion Cycle, Cash Holding and Creditworthiness. The term Cash Conversion Cycle can be considered as a length of time between purchase of raw-materials and collection of cash from debtors. Cash holding is one of the most important financial decisions that the manager of the concerned organization has to make for the organizations. In this paper, we try to interlink among different items to control cash so that bankruptcy could be prevented and profitability would be improved by investigating on five companies from Consumer Durable sector.